Role of College Principals in Promoting Quality of Education in District Kotli AJ&K - Saeed, Nauman; Kayani, Almas Ikram (Asian Journal of Contemporary Education, 2018)
The quality education is an indispensable and unavoidable instrument for change as education is a procedure of civilization and advancement. The main reason for the research was to find the role of college principals in promoting the quality of education in public colleges District Kotli AJ&K. It was a descriptive study of nature. All principals and teachers of public colleges of District Kotli AJ&K constituted the population of the study. The study was delimited to four tehsils. Two tehsils were selected for pilot testing and two for the final study. Consecutive sampling technique was used to draw the sample from population and sample was selected using L. R. Gay’s table of sampling. The data obtained were analyzed by using SPSS and AMOS software. The study explores that principals can play their vital role in improving the quality of education. Findings of the study show that enough availability of physical resources can be useful for enhancing the quality of education. The study revealed that administration, teacher’s job satisfaction also effects on quality of education. If college principals are willing to improve the quality of education, they should maintain positive relationships with their staff members. The study recommends that; all facilities should be provided, enough salary packages, accommodation, and transport facilities should be provided. Principals should cooperate with the staff. Both pre-service and in-service training is provided to the teachers. Managerial and administrative training should be provided to the principals.